Evaluasi Pedoman Penanganan Cepat Medis dan Kesehatan Masyarakat tentang Coronavirus Disease (COVID-19) di Indonesia - Maman Saputra; Miftahul Arsyi; Nurhanifah Nurhanifah; Syally Nadya Octavia; Hadi Pratomo (UIMA Press, 2020)
Abstract Introduction: In Indonesia the Coronavirus Disease (COVID-19) case has become a concern with the establishment of The Task Force of COVID-19 Handling Acceleration. The task force has developed guidelines for the quick handling of medical and public health. Objective: To field test the guidelines for medical and public health management regarding COVID-19 in Indonesia in terms of comprehension, attractiveness, acceptability, self involvement, and persuasion. Method: This is descriptive qualitative research. Informants were determined by purposive sampling of 5 informants. Data collection through in-depth interviews conducted virtually. The research instrument was developed by the research team in the form of guided in-depth interviews covering 5 aspects of pre-testing communication. Interview guidelines were tested on targets that had the same criteria with informants of 5 people. Data analysis was performed using thematic analysis. Results: The comprehension of health workforce regarding guidelines for medical and public health prompt management of COVID-19 in Indonesia is quite good, but difficult to understand for the community. On the dimension of attractiveness, these guidelines are quite attractive to health workforce but are less attractive to the community. This guideline is acceptable to both the health workforce and the community. Self-involvement of the health workforce and the commu-nity in this guideline is appropriate. This guideline persuades to change the behavior of the health work-force and the community. Conclusion: This guideline is suitable for health workers but needs some revision to make it easier to understand and attractive. This guideline is not suitable for the community because it is difficult to understand and not very attractive.